PARADIGMA KEILMUAN KPI DALAM PERSPEKTIF DAKWAH - Herdiana, Aan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2016)
Islamic Communication and Broadcasting or commonly known as KPI, as one of the majors in Islamic colleges, must have an identity. Basically, the KPIâ€™s scientific design can not be separated from two things, first, at the scientific level, the device is able to make science communication and science propaganda as the basis of activity design and the movement of Islamic broadcasting through various paradigmatic, theoretical, and methodological approaches. This is what is referred to as the ability of theoretical understanding (knowledge-based capability). Second, at a practical level, facilitating the growth of capabilities that could be the foundation undergraduate professional competence of KPI.Â Komunikasi dan penyiaran Islam atau yang biasa dikenal dengan KPI, sebagai salah satu jurusan di perguruan tinggi agama Islam, harus mempunyai identitas. Pada dasarnya desain keilmuan KPI tidak terlepas dari dua hal, Pertama, di level keilmuan, mampu menjadikan perangkat ilmu komunikasi dan ilmu dakwah sebagai basis dari desain aktivitas dan gerakan penyiaran Islam melalui berbagai pendekatan paradigmatik, teoritik, dan metodologis. Inilah yang disebut sebagai kemampuan pemahaman teoretik (knowladgebased capability). Kedua, di level praktis, memfasilitasi tumbuh kembangnya kemampuan yang dapat menjadi pijakan kompetensi profesi sarjana KPI.